Analisis Pengaruh Pendapatan Asli Daerah (PAD) Terhadap Kinerja Keuangan di Kabupaten Solok - Asma Ul Husna; Dessi Susanti (Jurnal Salingka Nagari, 2022)
This study plans to investigate: (1) local taxes on the implementation of regional financial performance (2) regional levies on financial performance (3) separate regional wealth results on financial performance (4) other PAD on financial performance. This exploration delegated a similar causal examination. The information used is the regional government financial plan (APBD) report and the 1990-2019 APBD revenue report distributed by the Directorate General of Fiscal Balance (DJPK). The exploration subjects are local taxes, regional levies, and the original PAD used is a quantitative investigation, with different relapse models. Speculation testing uses the F test, the measured t test is 5% and the straight difference test. Exploration shows that local revenue (PAD) has so far influenced the implementation of regional finance. However, to some extent, only other closest unique income affects financial performance, while environmental costs, necessitating isolated local organizational properties and resources have no effect on financial performance in Solok District